Sudden cardiac death in athletes: literature review of 2016 - O. Larintseva (Спортивная медицина: наука и практика)
Sudden cardiac death (SCD) in athletes isn't a frequent event, but, nevertheless, deserves a lot of attention from both the scientific community and health care professionals, coaches and athletes. The literature review showed that the problem of SCD still remains relevant because of its close association with physical activity and the lack of united standards of its screening, diagnostic and prevention. It is shown that the frequency of SCD varies widely depending on the population of the athlete, age and genetic characteristics, controversial is the question of the necessity and scope of a standard pre-season screening.